Summer Outdoor Thermal Perception for the Elderly in a Comprehensive Park of Changsha, China - Xinyi Li; Xiaoma Li; Na Tang; Simin Chen; Yuwan Deng; Dexin Gan (Atmosphere, 2022)
Thermal perception is an important factor affecting the usage of outdoor spaces (e.g., urban parks). The elderly are the main visitors of urban parks; however, few studies investigated the thermal perception of the elderly in urban parks in summer. Taking a comprehensive urban park in Changsha, China, as an example, this study examined the thermal perception of the elderly and investigated the impacts of age, gender, and health status on the thermal perception through field observation, questionnaires, and field measurement of meteorological variables. The results showed that: (1) The neutral physiological equivalent temperature (PET) was 24.48 °C, with a range of 21.99−26.97 °C. The comfortable PET was 25.41 °C, and the 90% acceptable PET was 25.84−33.19 °C. (2) The neutral PET increased with the elderly’s age (e.g., 23.19 °C, 25.33 °C, and 25.36 °C, respectively, for people aged 60–69, 70–79, and ≥80 years old). The thermal sensitivity of the elderly increased with the increase in age. (3) Moving to the shade provided by trees or buildings is the main thermal adaptation behavior of the elderly in the park in summer. This study extended the understanding of the outdoor thermal perception of the elderly in summer and can help better urban park planning and design to improve the thermal perception of elderly visitors in summer in Changsha (China).